Facilitating the C–C bond cleavage on sub-10 nm concavity-tunable Rh@Pt core–shell nanocubes for efficient ethanol electrooxidation. Issue 30 (15th July 2019) - Li, Pingting; Liu, Kai; Ye, Jinyu; Xue, Fei; Cheng, Yong; Lyu, Zixi; Liao, Xinyan; Wang, Wei; Zhang, Qiaobao; Chen, Xuejiao; Liu, Maochang; Xie, Shuifen
Abstract : Concavity-tunable Rh@Pt core–shell nanocubes with an engineered Rh–Pt interface and Pt atomic steps facilitate C–C bond cleavage in the EOR. Abstract : Sluggish C–C bond cleavage during the ethanol oxidation reaction (EOR) in acidic media results in a lowered energy yield and gravely hinders the commercialization of direct ethanol fuel cells. Here we report an elaborate synthesis of sub-10 nm concavity-tunable Rh@Pt core–shell nanocubes with an engineered Rh–Pt interface and Pt atomic surface steps to facilitate the C–C bond cleavage in the EOR. Using a microsyringe pump, the surface concavity of the Rh@Pt core–shell nanocubes is successfully manipulated through kinetically adjusting the ratio of the atom deposition rate and surface diffusion rate ( V dep. / V diff. ) during the overgrowth process. Compared to the samples with shallow surface concavity and a flat surface, the deeper concaved Rh@Pt core–shell nanocubes possess richer surface Pt atomic steps and exhibit a greater enhancement in EOR catalysis, achieving mass activity and specific activity that are 3.74 times and 6.89 times higher than those of the state-of-the-art Pt/C catalysts, respectively. Electrochemical in situ FTIR studies indicate that the Rh–Pt interfacial interaction and the surface Pt atomic steps on the Rh@Pt concave nanocubes can effectively facilitate the C–C bond cleavage towards the complete oxidation of ethanol to CO2 .